OCL constraints automatic generation for UML class diagram - Li Tan; Zongyuan Yang; Jinkui Xie (2010 IEEE International Conference on Software Engineering and Service Sciences, 2010)
As a standard modeling language of software architecture design, UML lacks formal semantics on account of its informal graphical notation. To further provide refined description of UML, OCL is primarily and widely employed. Generally, OCL constraints are written manually, which may cause incorrectness and extra overhead. Therefore, generating OCL constraints template for UML models is a superior solution. The OCL constraints template automatically generated can be used as a reference for software designers. First of all, the significance of automatic generation of OCL constraints was emphasized, and then the application domain of OCL was shown, followed by a lexical analysis of how to extract the target objects in UML models where OCL constraints were needed to build and an algorithm of extraction. Eventually, this extraction algorithm was implemented by Perl. In our way, the overall quality and efficiency of software design is enhanced and thus contributions are made for the automation of Software Engineering.